Elaboración de un video instruccional de los juegos tradicionales, para la difusión e interacción en los niños de la unidad educativa “Emilio Terán” del cantón Salcedo durante el periodo 2015-2016 - Araujo Espín, Adriana Vaneza (2016)
This research aims to rescue the traditional games of Ecuador by developing an instructional video. Information regarding the most popular games has been collected and selected. This information is presented clearly and accurately by using Multimedia and Design graphic Software in order to cover the audiovisual needs for traditional Ecuadorian games. Series of animations, illustrations, audio, video and text has been implemented in order to encourage children to persuade the information in a dynamic and entertaining way….